Covert recognition of familiar faces in an interocular suppression task. - Mejía Ramírez, Manuel Alejandro; Valdes Sosa, M.J.; Bobes León, A. (My University, 2021)
The Psychonomic Society is the preeminent society for the experimental study of cognition. Members are scientists who study how the mind works and advance the basic science of behavior in areas that include memory, learning, problem solving, decision making, language, attention, and perception. Many members are concerned with the application of psychology to health, technology, and education, and often use converging methods such as neuroscience and computational science to achieve their research goals. Their work also connects with research in biology, chemistry, statistics, computer science, medicine, law, and business.
Keywords: Interocular; Suppression